2023
DOI: 10.1108/ara-01-2023-0015
|View full text |Cite
|
Sign up to set email alerts
|

A survey study of Iraqi auditors' adoption of blockchain technology

Rasha H. Majeed,
Alaa A.D. Taha

Abstract: PurposeThis paper seeks to investigate the factors influencing auditors' behavioural intentions towards blockchain technology (BT) adoption in Iraqi government banks. It also highlights the relationships between these factors to determine if the proposed model can provide a more comprehensive means of comprehending how auditors in government banks have adopted BT.Design/methodology/approachThe study uses the unified theory of acceptance and use of technology and expands it by incorporating five external constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Previous literature found that BT is one of the main antecedents for users' intentions towards using Blockchain technology (e.g. Kamble et al, 2020;Sahebi et al, 2022;Majeed and Taha, 2023;Tran and Nguyen, 2021). Therefore, the subsequent hypothesis was proposed:…”
Section: Blockchain Transparencymentioning
confidence: 99%
“…Previous literature found that BT is one of the main antecedents for users' intentions towards using Blockchain technology (e.g. Kamble et al, 2020;Sahebi et al, 2022;Majeed and Taha, 2023;Tran and Nguyen, 2021). Therefore, the subsequent hypothesis was proposed:…”
Section: Blockchain Transparencymentioning
confidence: 99%